MELANVEER : TEKNOLOGI PENDETEKSI PEMBULUH DARAH VENA UNTUK MENINGKATKAN PELAYANAN KESEHATAN) - Adeline, Ivone; Maulana, Andri; Hartriningsih, Salzabila; Adi Prasetyanto, Wisnu (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Intravenous (IV) procedures face challenges due to low nurse proficiency (50.8%) in Indonesian and difficulties in vein visualization, especially in patients with darker skin tones. Objectives: To develop an affordable, portable vein detection device,